Sustainability Strategies in Clusters and the Role of Communication - Marco Bettiol; Greta Buoso; Eleonora Di Maria (Investigaciones Regionales - Journal of Regional Research)
Environmental sustainability impacts on industrial districts and their lifecycle evolutionary processes. Nevertheless, research in this direction is scant, suggesting on the one hand, the role of lead ﬁrms of global value chains and, on the other hand, potential contributions of suppliers. e paper explores how district ﬁrms have invested in sustainability by analyzing sustainable-oriented communication strategies (certiﬁcation, web, exhibitions) of Italian leather and jewelry clusters. Results show that districts are evolving by including sustainability in their strategies. A variety of sustainability strategies emerge among district ﬁrms, with diﬀerences also between ﬁrms in B2B and B2C markets.